PASSIVE EUTHANASIA ON INDONESIA LAW AND HUMAN RIGHTS - Tomy Pasca Rifai (Universitas Muhammadiyah Metro, 2018)
Discussion regarding passive euthanasia is strongly related to the law and human rights as noted in the Article 6 (1) International Covenant on Civil and Political Rights assert that “Every human being has the inherent right to life. This right shall be protected by law. No one shall be arbitrarily deprived of his life” which has been ratified by Indonesia Law No. 12 of 2005. Hence, this research perspective mainly focuses on the law regarding medical issues especially the passive euthanasia, which occurs indirectly from a doctor with the request or consent of the patient and/or the family to refuse, discontinue, or reject medical efforts. Further, there are two types of legal relationships between patients and doctors in the health services, which is contractual and the therapeutic relationship in relation to laws and regulations, i.e the regulation of the Minister of Health No. 37 of 2014, Law of Health No. 36 of 2009, Law of Medical Practices No. 29 of 2004 and the Indonesia code of medical ethics which states that